The Case Study Of JHKM Harness Sdn Bhd - Ooi, Eisen Ban Hoo (2007)
This study will enable us to have clearer picture of JHKM as a whole. Besides, we will also study the industry where JHKM operates in to understand the business in wire harness and manufacturing industry.